Controllability of second-order nonlocal retarded semilinear systems with delay in control. Issue 16 (9th December 2020) - Haq, Abdul; Sukavanam, N.
ABSTRACT: This article is concerned with the second-order nonlocal retarded semilinear differential systems with fixed delay in control. Utilizing the theory of fixed point as well as cosine family, we establish the existence and uniqueness of the mild solution of the system. Then a set of new sufficient conditions are established for the controllability of the semilinear system. The theory is illustrated by providing an example.